PEMBELAJARAN BIOLOGI DENGAN METODE FREQUENT PRACTICAL WORK TERHADAP TINGKAT SELF EFFICACY DAN HASIL BELAJAR KOGNITIF SISWA SMA - Risela Karismania; Jujun Ratnasari; Gina Nuranti (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
This study aims to determine the level of effectiveness of the Frequent Practical Work learning method on the level of Self Efficacy and cognitive learning outcomes of high school students. Frequent Practical Work or repetitive work practices are carried out in various ways. In this study, practical work refers to the teaching and learning activities of biology. This research was conducted in one of the senior high schools in the city of Sukabumi with a research sample of 24 students in the control class and 26 students in the experimental class. In the control, class learning is done using conventional methods while in the experimental class learning is done using the Frequent Practical Work learning method. The results show that the level of effectiveness of the Frequent Practical Work learning method in the experimental class is quite effective for learning. In the experimental class, the level of Self Efficacy is in the high category, while in the control class the level of Self Efficacy is in the medium category. In the experimental class, the students' cognitive learning outcomes have a higher class average than in the control class.Kata Kunci : Hasil belajar Kognitif, Frequent Practical Work, Self Efficacy,